FENOMENA FLYPAPER EFFECT PADA PROVINSI YANG MENGALAMI PEMEKARAN DI INDONESIA - Rambe, Roosemarina Anggraini; Purmini; Hutapia (Lembaga Penerbit Fakultas Ekonomi dan Bisnis, 2023)
1)To analyze the effect of local revenue (PAD), resource sharing fund (DBH), general grants (DAU), and special grants (DAK) on the local government spending in blooming provinces in Indonesia. 2) To analyze the flypaper effect phenomenon in blooming provinces in Indonesia. This research is exploratory research. The data used is panel data, consisting of 25 blooming provinces from 2014-2020. The analysis method applied is panel data regression. The dependent variable is government spending, while the independent variables used are local revenue (PAD), resource sharing fund (DBH), general grants (DAU), and special grants (DAK). Local revenue (PAD), general grants (DAU), and special grants (DAK) have a positive effect significantly on government expenditures. While resource sharing fund (DBH) does not have an effect on government expenditures. Furthermore, there is no flypaper effect phenomenon in blooming provinces in Indonesia. Flypaper effect, local revenue (PAD), resource sharing fund (DBH), general grants (DAU), special grants (DAK).